Patients' awareness of antibiotic use in Bahraini health centers and community pharmacies - Sayed Mahmood Alqallaf; Win Winit-Watjana (Archives of Global Professionals, 2015)
Objective: Patients' understanding and perceptions of antibiotic use and resistance are crucial for the public health. This study aimed to explore the awareness of antibiotic utilization in 12 aspects among Bahraini patients attending health centers and community pharmacies and to find the associations of their awareness. Materials and Methods: A cross-sectional survey study with questionnaire interviews was conducted in Bahraini patients attending five health centers or four community pharmacies during January - June 2013. All data were analyzed using descriptive statistics and a Chi-squared test was performed with a significance level set at 0.05. Results: A total of 306 patients (156 in health centers and 150 in community pharmacies) participated in the study. Female respondents (57.2%) were nearly equal to the male. Most were adults aged 16-29 (47.7%) and educated at the university or school levels (88.2%). The majority were aware of the use for colds and relevant resistance, including 10 other aspects. Approximately 35% misconceived the medicine intake in terms of concomitant use with milk, daily doses, stopping time and reusability. Patients' education was associated with six aspects of awareness, that is, decision on antibiotic prescribing, drug administration, treatment duration, drug resistance, reusability, and perceived side-effects (all P < 0.05). Conclusion: Bahraini patients are mostly aware of 12 antibiotic aspects despite some misconceptions. The public awareness and their expectations warrant further studies on a large scale to understand their self-medication and demand for antibiotic prescriptions.